Training on Animated English Material Development Using Video Scribe for Second-Semester English Education Students - Halawa, Arif Wahyu; Mawati Zai, Irene Netalis; Zendrato, Oktoberlianus; Telaumbanua, Yasminar Amaerita (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2025)
The use of animation-based digital tools has grown more and more important in preparing pre-service teachers for classrooms in the twenty-first century. This study examines the efficacy of a focused training program that exposed Nias University English education students to Videoscribe, an animated instructional video creation tool. The program focused on learning through practice, reflection, and visual-verbal integration, and it was based on the experiential learning theory (Kolb, 1984) and multimedia learning theory (Mayer, 2021). A hands-on session with a descriptive qualitative approach was attended by nine participants. Field notes, observation checklists, and questionnaires were used to gather data. The results demonstrated that when utilizing VideoScribe to teach English, participants' technical proficiency, pedagogical knowledge, and self-confidence all significantly improved. These difficulties show how important ongoing mentoring and scaffolded help are. According to the study's findings, short-term, hands-on training can help close the knowledge gap between theory and digital teaching proficiency. Additionally, it adds to the increasing amount of data supporting the inclusion of digital media literacy in teacher preparation programs. The consequences go beyond curriculum design and policy-making, indicating that in order to foster future educators' confidence and inventiveness, technology integration should be methodically incorporated into teacher training programs.